ANALISIS MOTIVASI KERJA APARATUR PEMERINTAH DI KANTOR KECAMATAN DAPURANG KABUPATEN MAMUJU UTARA - Elsi, Elsi (Katalogis, 2015)
The purpose of this study was to determine the Work Motivation Government Personnel At the District Office Dapurang North Mamuju regency. This type of research is descriptive qualitative approach derived from the results of in-depth interviews. The location of research at the District Office Dapurang North Mamuju regency. Research informant as much as 5 (five) employees with data sources include primary data and secondary data and data collection through interviews, observation, and documentation. The data analysis using descriptive data analysis model with a qualitative approach. The results showed that the motivation of employees, already well motivated employees work to serve the community in accordance with their respective duties because of a desire to meet the needs for achievement, need for power, and the company needed to be affiliated. Then the results of research in the field find the reality that job performance, promotion and collaboration with colleagues is a driver of employee motivation. However, some employees still lack motivation to gain power